Epigenetic Regulation of Angiogenesis in Development and Tumors Progression: Potential Implications for Cancer Treatment - Aspriţoiu, Veronica Mãdãlina; Stoica, Ileana; Bleotu, Coralia; Diaconu, Carmen Cristina (Frontiers in Cell and Developmental Biology, 2021)
Angiogenesis is a multi-stage process of new blood vessel development from pre-existing vessels toward an angiogenic stimulus. The process is essential for tissue maintenance and homeostasis during embryonic development and adult life as well as tumor growth. Under normal conditions, angiogenesis is involved in physiological processes, such as wound healing, cyclic regeneration of the endometrium, placental development and repairing certain cardiac damage, in pathological conditions, it is frequently associated with cancer development and metastasis. The control mechanisms of angiogenesis in carcinogenesis are tightly regulated at the genetic and epigenetic level. While genetic alterations are the critical part of gene silencing in cancer cells, epigenetic dysregulation can lead to repression of tumor suppressor genes or oncogene activation, becoming an important event in early development and the late stages of tumor development, as well. The global alteration of the epigenetic spectrum, which includes DNA methylation, histone modification, chromatin remodeling, microRNAs, and other chromatin components, is considered one of the hallmarks of cancer, and the efforts are concentrated on the discovery of molecular epigenetic markers that identify cancerous precursor lesions or early stage cancer. This review aims to highlight recent findings on the genetic and epigenetic changes that can occur in physiological and pathological angiogenesis and analyze current knowledge on how deregulation of epigenetic modifiers contributes to tumorigenesis and tumor maintenance. Also, we will evaluate the clinical relevance of epigenetic markers of angiogenesis and the potential use of “epi-drugs” in modulating the responsiveness of cancer cells to anticancer therapy through chemotherapy, radiotherapy, immunotherapy and hormone therapy as anti-angiogenic strategies in cancer.